Misperceived quality: fertilizer in Tanzania - Michelson, H.; Fairbairn, A.; Ellison, B.; Maertens, A.; Manyong, Victor (Elsevier, 2021)
Fertilizer use remains below recommended rates in most of Sub-Saharan Africa, contributing to low crop yields and poverty. We explore the role of fertilizer quality. We interviewed fertilizer sellers in an important agricultural region in Tanzania and sampled their fertilizer to establish that the nutrient content of fertilizers is good, meeting industry standards. However, we find farmers’ beliefs to be inconsistent with this reality. Beliefs about adulteration push down farmer willingness-to-pay for fertilizer; with farmers willing to pay more if quality is verified. In addition, we find some evidence of a quality inference problem: many fertilizers have degraded appearance, and farmers appear to rely on these observable attributes to (incorrectly) assess unobservable nutrient content. Market prices reflect neither nutrient content nor degradation in appearance, even in competitive markets. Our results suggest the existence of an equilibrium where farmer beliefs about fertilizer are inconsistent with the truth, and seller incentives to invest to alter beliefs are limited, motivating future research into the origins and persistence of such an equilibrium.